Perfusate Liver Arginase 1 Levels After End-Ischemic Machine Perfusion Are Associated with Early Allograft Dysfunction - Giuseppina Basta; Serena Babboni; Daniele Pezzati; Serena Del Turco; Emanuele Balzano; Gabriele Catalano; Lara Russo; Giovanni Tincani; Paola Carrai; Stefania Petruccelli; Jessica Bronzoni; Caterina Martinelli; et al. (Biomedicines)
Background/Objectives: The rising use of liver grafts from donation after circulatory death (DCD) has been enabled by advances in normothermic regional perfusion (NRP) and machine perfusion (MP) technologies. We aimed to identify predictive biomarkers in DCD grafts subjected to NRP, followed by randomization to either normothermic machine perfusion (NMP) or dual hypothermic oxygenated perfusion (D-HOPE). Methods: Among 57 DCD donors, 32 liver grafts were transplanted, and recipients were monitored for one week post-transplant. Biomarkers linked with oxidative stress, hepatic injury, mitochondrial dysfunction, inflammation, regeneration, and autophagy were measured during NRP, end-ischemic MP, and one week post-transplant. Results: Arginase-1 (ARG-1) levels were consistently higher in discarded grafts and in recipients who later developed early allograft dysfunction (EAD). Specifically, ARG-1 levels at the end of MP correlated with markers of hepatic injury. Receiver operating characteristic analysis indicated that ARG-1 at the end of MP had a good predictive accuracy for EAD (AUC = 0.713; p = 0.02). Lipid peroxidation (TBARS) elevated at the start of NRP, declined over time, with higher levels in D-HOPE than in NMP, suggesting a more oxidative environment in D-HOPE. Metabolites like flavin mononucleotide (FMN) and NADH exhibited significant disparities between perfusion types, due to differences in perfusate compositions. Inflammatory biomarkers rose during NRP and NMP but normalized post-transplantation. Regenerative markers, including osteopontin and hepatocyte growth factor, increased during NRP and NMP and normalized post-transplant. Conclusions: ARG-1 demonstrates strong potential as an early biomarker for assessing liver graft viability during perfusion, supporting timely and effective decision-making in transplantation.